8.78% Efficient All‐Polymer Solar Cells Enabled by Polymer Acceptors Based on a B←N Embedded Electron‐Deficient Unit. Issue 44 (18th September 2019) - Li, Yongchun; Meng, Huifeng; Liu, Tao; Xiao, Yiqun; Tang, Zhonghai; Pang, Bo; Li, Yuqing; Xiang, Ying; Zhang, Guangye; Lu, Xinhui; Yu, Gui; Yan, He; et al.
Abstract: In the field of all‐polymer solar cells (all‐PSCs), all efficient polymer acceptors that exhibit efficiencies beyond 8% are based on either imide or dicyanoethylene. To boost the development of this promising solar cell type, creating novel electron‐deficient units to build high‐performance polymer acceptors is critical. A novel electron‐deficient unit containing B←N bonds, namely, BNIDT, is synthesized. Systematic investigation of BNIDT reveals desirable properties including good coplanarity, favorable single‐crystal structure, narrowed bandgap and downshifted energy levels, and extended absorption profiles. By copolymerizing BNIDT with thiophene and 3, 4‐difluorothiophene, two novel conjugated polymers named BN‐T and BN‐2fT are developed, respectively. It is shown that these polymers possess wide absorption spectra covering 350–800 nm, low‐lying energy levels, and ambipolar film‐transistor characteristics. Using PBDB‐T as the donor and BN‐2fT as the acceptor, all‐PSCs afford an encouraging efficiency of 8.78%, which is the highest for all‐PSCs excluding the devices based on imide and dicyanoethylene‐type acceptors. Considering that the structure of BNIDT is totally different from these classical units, this work opens up a new class of electron‐deficient unit for constructing efficient polymer acceptors that can realize efficiencies beyond 8% for the first time. Abstract : An electron‐deficient unit containing B←N bonds, namely BNIDT, is developed to construct polymer acceptors for photovoltaic applications. Desirable optoelectronic properties such as broad absorption profiles, low‐lying energy levels, ambipolar charge transport properties, and strong electron‐affinity are found for these polymers. All‐polymer solar cells using these B←N embedded polymers as acceptor materials exhibit an enhanced efficiency of 8.78%.